2008
DOI: 10.1021/ja0779607
|View full text |Cite
|
Sign up to set email alerts
|

Carbon−Deuterium Bonds as Probes of Dihydrofolate Reductase

Abstract: Much effort has been directed towards understanding the contributions of electrostatics and dynamics to protein function and especially to enzyme catalysis. Unfortunately, these studies have been limited by the absence of direct experimental probes. We have been developing the use of carbon-deuterium bonds as probes of proteins and now report the application of the technique to the enzyme dihydrofolate reductase, which catalyzes a hydride transfer and has served as a paradigm for biological catalysis. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
89
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 56 publications
3
89
3
Order By: Relevance
“…The functional importance of CH⋅⋅⋅O hydrogen bonding in AdoMet‐dependent methyltransferases has been argued,7 but a link to KIEs has not been previously proposed. It is known, however, that CD bond stretching frequencies are sensitive to the local electric field within a protein environment 16. Klinman and co‐workers have reported T 3 KIEs on k cat / K m in human COMT: 0.791±0.012 for the wild‐type enzyme and 0.822±0.021 and 0.850±0.012 for its Y68F and Y68A mutants, respectively 2, 3.…”
mentioning
confidence: 99%
“…The functional importance of CH⋅⋅⋅O hydrogen bonding in AdoMet‐dependent methyltransferases has been argued,7 but a link to KIEs has not been previously proposed. It is known, however, that CD bond stretching frequencies are sensitive to the local electric field within a protein environment 16. Klinman and co‐workers have reported T 3 KIEs on k cat / K m in human COMT: 0.791±0.012 for the wild‐type enzyme and 0.822±0.021 and 0.850±0.012 for its Y68F and Y68A mutants, respectively 2, 3.…”
mentioning
confidence: 99%
“…While IR frequency shifts associated with various environments can be considered at a qualitative level (e.g., is the probe buried or on a solvent exposed surface?7,8), our goal has been to extract quantitative information on electric fields in proteins1,2. Although several studies have suggested a connection between observed vibrational band shifts and local electrostatic fields due to the organized environment around the probe3,6, in the absence of an independent experimental test it remains uncertain whether these shifts are due principally to electrostatic effects or are dominated by contributions from specific chemical interactions9, such as hydrogen bonds. We report herein a method for identifying and quantifying departures from an electrostatic mechanism for nitrile vibrational shifts that utilizes the relationship between IR frequency shifts and 13 C NMR chemical shifts and demonstrate its utility in a protein.…”
mentioning
confidence: 99%
“…This latter approach has been applied to DHFR in a previous study wherein all but one methionine was mutagenized to leucine to allow for site-specific labeling. [23] In order to examine a residue such as Tyr100 in DHFR without the introduction of potentially perturbative mutations, we now report the use of a biosynthetic method to site-selectively incorporate a photocaged, deuterated amino acid, which after photolysis yields the site-selectively deuterated, but otherwise natural protein.…”
mentioning
confidence: 99%